PENERAPAN METODE AVERAGE BASED LENGTH FUZZY TIME SERIES LEE UNTUK PREDIKSI KECEPATAN ANGIN DI KABUPATEN NATUNA - Dela Nifari; Nurfalinda Nurfalinda; Muhamad Radzi Rathomi (Faktor Exacta, 2025)
Wind speed is a critical parameter that significantly affects the safety of maritime activities, particularly in Natuna Regency, a strategic region with substantial marine potential. This study aims to predict wind speed in Natuna Regency using the Average Based Length Fuzzy Time Series Lee method. The data utilized in this research consists of the average wind speed data for Natuna Regency obtained from the Meteorological Station of BMKG Ranai, covering the period from January 1, 2023, to December 31, 2023, comprising 365 data points. The interval length in the process significantly influences the prediction results. Based on testing, the model achieved a Mean Absolute Percentage Error (MAPE) of 24.42% with an accuracy rate of 78.05%, indicating that the Average Based Length Fuzzy Time Series Lee method demonstrates a reasonably good level of forecasting accuracy for predicting wind speed in Natuna Regency.